Preparation of Starch-Chitosan Nanocomposites for Control Drug Release of Curcumin (International Journal of Current Engineering and Technology, 2015)
In the present research program, novel nanocomposites of Starch, which is one of the most abundant polysaccharides polymer, which blended with the Chitosan has been carried out varying the proportion of MMT (Cloisite 30B) were prepared. The blending of the two polymers has been carried out varying the proportion of nanoclay so that the composite can be a better drug carrier. The blends were characterized by Fourier Transmission Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Xray Diffraction (XRD) analysis. The swelling studies have been carried out at different drug loading. Swelling study is an important parameter to predict the diffusion of the drugs from the matrix. The kinetics of the drug delivery system has been systematically studied. Drug release kinetics was analyzed by plotting the cumulative release data versus time by fitting to an exponential equation which indicated the non-Fickian type of kinetics. The drug release was investigated at different pH medium, and it was found that the drug release depends upon the pH medium as well as the nature of matrix
Keywords: Starch; Chitosan; Curcumin; Nanocomposite; Drug delivery